The effect of Azorhizobium caulinodans ORS571 and γ-aminobutyric acid on salt tolerance of Sesbania rostrata - Liu, Yanan; Liu, Xiaolin; Dong, Xiaoyan; Yan, Jiaming; Xie, Zhihong; Luo, Yongming (Frontiers in Plant Science, 2022)
Salt stress seriously affects plant growth and crop yield, and has become an important factor endangering soil quality worldwide. In recent years, the cultivation of salt-tolerant plants such as Sesbania rostrata has a positive effect on improving coastal saline-alkali land. Microbial inoculation and the GABA addition have been shown to enhance the plant tolerance in response to the abiotic stresses, but studies in green manure crops and the revelation of related mechanisms are not clear. In this study, the effects of inoculation with Azorhizobium caulinodans ORS571 and exogenous addition of γ-Aminobutyric Acid (GABA) (200 mg·L-1) on the growth and development of S. rostrata under salt stress were investigated using potting experiments of vermiculite. The results showed that inoculation with ORS571 significantly increased the plant height, biomass, chlorophyll content, proline content (PRO), catalase (CAT) activity and superoxide dismutase (SOD) activity of S. rostrata and reduced the malondialdehyde (MDA) level of leaves. The exogenous addition of GABA also increased the height, biomass, CAT activity and reduced the MDA and PRO level of leaves. In addition, exogenous addition of GABA still had a certain improvement on the CAT activity and chlorophyll content of the ORS571-S. rostrata symbiotic system. In conclusion, inoculation of ORS571 and addition of GABA have cooperative positive effects on improving the salt stress resistance of S. rostrata by increasing the activity of antioxidant enzymes and reducing the content of MDA. This study provided a potential biological way for the restoration of saline-alkali soil.